T&T Clark handbook to early Christian meals in the Greco-Roman world - Al-Suadi, Soham 1980-; Smit, Peter-Ben 1979- (T&T Clark, 2019)
Meals are a highly significant element in the development of Christian identity. In this handbook Soham Al-Suadi and Peter-Ben Smit present chapters that situate early Christian meals in their broader context, with a focus on the core topics that will help us to understand Greco-Roman meal practice and how this relates to Christian origins. The issues covered include: the role of gender during meals; issues of monotheism and polytheism that arise from the structure of the meal; how sacrifice is understood in different meal practices; power dynamics during the meal and issues of inclusion and exclusion at meals. In addition to looking at the broader Hellenistic context the chapters explain the unique nature of Christian meals, and what this says about early Christian communities. The handbook is structured around the key primary resources, with the literary, historical, theological and philosophical aspects of these resources being considered in turn. The handbook begins with Hellenistic documents/authors before moving on to the New Testament material itself according to genre (Gospels, Acts, Letters, Apocalyptic Literature). Finally, there is a section on the wider resources that describe daily life in the period (medical documents, inscriptions). This structure enables the editors and contributors to present an analysis of the social values exhibited at meals and their significance for early Christian theology